Unveiling the neural mechanisms of acute aerobic exercise on inhibitory control among young adults with obesity: Insights from an ERP study - Kun Wang; Shaobo Cai; Tao Huang; Zhangyan Deng; Jiali Qian; Yanxia Chen; Guozhuang Chen; Lei Xu; Peisi Wang; Yuhan Zhang; Yuhan Qiu; Chun Xie (Acta Psychologica)
Obesity has become a prominent public health concern worldwide and is associated with adverse cognitive function. Exercise, particularly aerobic exercise, is known to benefit for weight loss and cognitive function. However, whether acute aerobic exercise could yield benefits to obese individuals and the precise brain mechanisms of action remain poorly understood. The study aimed to investigate whether acute aerobic exercise could improve inhibitory control among obese individuals and what neuroelectric mechanisms are implicated. A 3 (session: control, low-intensity exercise, moderate-intensity exercise) × 2 (congruency: congruent, incongruent) within-subject design was conducted. 18 obese young male adults underwent three sessions of 30-min interventions in a counterbalanced order seperated by five days: moderate-intensity aerobic exercise (MIE), low-intensity aerobic exercise (LIE) and a control session (a sedentary period of seated rest). The Flanker task and EEG recordings (N2 and P3 amplitude) were investigated following exercise and the control treatment. Results showed that the N2 amplitude following MIE was larger than the control session, whereas a larger N2 and reduced congruent P3 amplitude was observed following MIE than LIE. However, no main effect of the session was found for reaction time and accuracy, but a significant main effect of congruency was observed. These findings suggest acute moderate-intensity aerobic exercise may modulate brain activity through enhanced recruitment of attentional resources for cognitive control and conflict monitoring in adults with obesity.